A fast self-calibration method of line laser sensors for on-machine measurement of honeycomb cores. (May 2022) - Qin, Yan; Kang, Renke; Sun, Jiansong; Wang, Yidan; Zhu, Xianglong; Dong, Zhigang
Highlights: The introduced method can work without the help of precision apparatus. The calibration and surface scanning are separated to achieve high efficiency. The experimental stitching error verified through a solid block is less than 8 μm. Abstract: Line laser scanning is an effective method used to measure the 3D shape of machined honeycomb core surfaces. The lack of laser-sensor calibrations in 3D space relative to the machine coordinate system restricts the industrial applications of line lasers for on-machine measurements. In this paper, a sensor calibration method based on scanning a honeycomb core itself is proposed. The sensor rotational errors are reversely calculated from the data dislocation originating from the sensor without calibration, and then calibrated by mechanical adjustment and numerical compensation. The sensor calibration parameters are determined once rather than performing data stitching one by one, greatly improving the operation efficiency. The sensor calibration effect is verified from the data seam analysis with and without sensor calibration as well as without stitching, and the comparison results demonstrate that the proposed method is effective in solving the misalignment of the measurement data after stitching. The experimental stitching error verified through a solid block is less than 8 μm. The proposed self-calibration stitching method possesses advantages in large-sized on-machine measurements of honeycomb cores.